Evaluating ion exchange for nitrogen recovery from source-separated urine in Nairobi, Kenya. (2018) - Tarpeh, William A.; Wald, Ileana; Omollo, Michael Otieno; Egan, Timothy; Nelson, Kara L.
Abstract: Rapid population growth in developing world urban centers outpaces provision of essential services such as excreta collection and treatment. Separate collection of urine and feces and decentralized treatment can potentially serve more households at lower energy and cost than conventional waterborne sewers and treatment plants. We conducted a technical validation and preliminary economic modeling to evaluate ion exchange columns, one technical option for recovering nitrogen from urine in Nairobi, Kenya. This technology could be combined with phosphorus recovery and a disinfection step to allow local discharge of the treated urine. Performance, as measured by adsorption density (4.02–4.21 mmol N/g resin) and regeneration efficiency (>90%) of the adsorbent, was consistent over ten adsorption-regeneration cycles and with columns ten times larger than lab-scale (65 L/d vs. 6.5 L/d). Effluent absorbance and electrical conductivity were identified as indicators of urine and ammonia breakthrough, respectively; both parameters are lower cost and easier to measure on-line than ammonium concentrations. Urine storage containers should be closed to avoid changes in urine composition, including loss of ammonia (and thus potential revenue). Treatment of urine by ion exchange is 40% less expensive than disposal without treatment and urine-derived ammonium sulfate was produced well below market costs of commercial fertilizers.